Penggunaan Instagram Live BeritaBaik. Id dalam Program Bicara Baik - Miranda Shafira Alamsyah; Aat Ruchiat Nugraha (LUGAS Jurnal Komunikasi, 2022)
This study examines the usage of Beritabaik.id Live Instagram in the Bicara Baik program. The purpose of this study is to find out and explain the participation, interactivity, and content of messages conveyed in Bicara Baik Live Instagram with the Mental Act Community. The author uses participant observation techniques, interviews and literature studies in collecting data in this writing. The results of the collection of study materials and analysis led to the conclusion that participation in Bicara Baik Live Instagram with the Mental Act Community is still very low. From the two episodes with the Act Mental community, there are only 0.4-0.5% of Beritabaik.id followers who participate in Bicara Baik Live Instagram. Even so, interactivity has been well established between the hosts, speakers and audience. This is evidenced by the comments and questions given by the audience and then responded to by the speakers. In fact, the communication pattern that exists on Bicara Baik Live Instagram is a circular communication pattern. This is because from every interaction that is built, it doesn't just stop at the audience. Instead, the audience sends the message back to the source. In addition, the content of the message conveyed is in accordance with the Live Instagram theme that is carried. The viewers who watched Live Instagram with the Act Mental Community clearly knew the important educational points conveyed by the speakers from the two episodes.